High Mean Platelet Volume Associates with In-Hospital Mortality in Severe Pneumonia Patients. (8th June 2020) - Chen, Jieru; Li, Yihao; Zeng, Yingsi; Tian, Yu; Wen, Yueqiang; Wang, Zebin
Abstract : Background . Although mean platelet volume (MPV) appears to be associated with poor outcome of pneumonia, the relationship between MPV and in-hospital mortality is unclear in severe pneumonia (SP) patients. Methods . In this retrospective cohort study, 115 SP patients from June 1st, 2016, to September 29th, 2019, were included and divided into two groups. The primary outcome was in-hospital mortality. The receiver operating characteristic (ROC) curve was performed to assess the predictive ability for in-hospital mortality. Kaplan-Meier cumulative incidence curves were applied to observe the incidence of mortality. Multivariable Cox regression analyses were used to evaluate the hazard ratios (HRs). Besides, a formal test for interaction was investigated to analyze the relationship between MPV and sex. Results . During the course of hospitalization, 63 cases of mortality were recorded. ROC analysis suggested that MPV had a modest power for predicting in-hospital mortality (AUC = 0.723, 95% CI: 0.628-0.818, P < 0.001 ). Yet the cutoff value of MPV was 10.5 (sensitivity = 73.02 %; specificity = 73.08 %). Compared to the low-MPV group, the high-MPV group had significantly increased in-hospital mortality (log-rank test = 13.501, P < 0.001 ), while the adjusted Cox model indicated that the high-MPV group was associated with an elevated risk of in-hospital mortality (HR: 2.267, 95% CI: 1.166-4.406, P = 0.016 ). Moreover, analyses of in-hospital mortality suggested a significant interaction between optimal MPV level and sex (P = 0.011 ). In a multivariate Cox model which included females only, a high MPV level was associated with increased risk of in-hospital mortality (HR: 11.387, 95% CI: 1.767-73.380, P = 0.011 ). Conclusion . High MPV level is an independent risk factor for in-hospital mortality in patients with SP.